Use of dielectric nanoparticles doped with Yb3+ ions to enhance the thermal effect in a biological tissue exposed to near-IR laser radiation (in vivo experiments). (November 2021) - Ryabochkina, P.A.; Khrushchalina, S.A.; Belyaev, A.N.; Bushukina, O.S.; Yurlov, I.A.; Kostin, S.V.
Abstract: The conditions for the appearance of broadband radiation from particles of zirconium dioxide stabilised by ytterbium oxide upon excitation by intense laser radiation with a wavelength of 980 nm are investigated. It is shown that this radiation is observed at a lower excitation power density and lower ytterbium content than in particles of orthophosphates and their hydrates. As a result of in vivo experiments, the possibility of using ytterbium-containing particles to enhance the thermal effect from exposure to laser radiation with a wavelength of 980 nm on the skin of a rat is demonstrated.